Tailoring sputter grown NiOx layer by synergistic surface passivation for efficient perovskite solar cells - Yadav K.; Samanta A.; Ankita; Tarun; Das S.; Kanjilal A.; Pandey U.K. (My University, 2025)
Sputtered nickel oxide serves as an appealing hole-transport layer for effective and stable p-i-n perovskite solar cells due to its ameliorated mobility of hole, outstanding stability, ease of fabrication and favourable fermi level for proficient transfer of holes. Nevertheless, unfavourable chemical reactions and surface traps at the sputter grown NiOx/perovskite interface hinder its performance. To address these challenges concurrently, a novel passivation approach for the sputter grown NiOx/perovskite interface has been demonstrated by utilizing a self-assembled monolayer of [2-(9H-carbazol-9-yl) ethyl]phosphonic acid (2PACz). We found that the 2PACz based passivation layer not only enhances the morphology of perovskite film with ameliorated domain size, it also diminishes carrier recombination amid sputter grown NiOx/perovskite interface, mitigating surface defects of the sputter grown NiOx film. Additionally, 2PACz layer acts as an impediment for detrimental chemical reactions at the sp-NiOx/perovskite interface, improving the overall device stability. Consequently, the power conversion efficiency was enhanced from 14.94 % in the base device to 16.59 % after the surface passivation of sputter grown NiOx/perovskite interface with 2PACz. © 2025 International Solar Energy Society